The Impact of Unit Trust Management Company Fund Investment on Investors’ Risk - Teoh, Teng Tenk (Asian Journal of Business and Accounting, 2012)
Investors in Malaysia tend to invest in unit trusts in a single Management Company because of the limited number of Management Companies. This study evidences that unit trust returns are more closely correlated within the funds of the company than across different companies. An increase in asset correlation lowers the diversification benefits for investors. Hence, investing in funds managed by the same Management Company increases the total portfolio risk and reduces diversification. This finding is in tandem with the U.S. evidence. It is concluded that Malaysian unit trust investors should avoid investing their money in funds in the same Management Company, even though by doing so they are able to enjoy a very low switching fees benefit and easier management of funds. Additionally, investors are also advised to diversify their portfolio by integrating their investment of conventional funds with Islamic funds. It is also noted that Money Market funds stand out as good diversification due to their low correlation with the other funds. Keywords: Correlation, Common holdings, Diversification, Islamic, Malaysia, Risk, Unit Trusts Companies